Ruthenium(II)‐Catalyzed C−H Activation of Imidamides and Divergent Couplings with Diazo Compounds: Substrate‐Controlled Synthesis of Indoles and 3H‐Indoles. Issue 39 (25th August 2016) - Li, Yunyun; Qi, Zisong; Wang, He; Yang, Xifa; Li, Xingwei
Abstract: Indoles are an important structural motif that is commonly found in biologically active molecules. In this work, conditions for divergent couplings between imidamides and acceptor–acceptor diazo compounds were developed that afforded NH indoles and 3 H ‐indoles under ruthenium catalysis. The coupling of α‐diazoketoesters afforded NH indoles by cleavage of the C(N2 )−C(acyl) bond whereas α‐diazomalonates gave 3 H ‐indoles by C−N bond cleavage. This reaction constitutes the first intermolecular coupling of diazo substrates with arenes by ruthenium‐catalyzed C−H activation. Abstract : Which way to go : NH indoles and 3 H ‐indoles were synthesized by ruthenium(II)‐catalyzed C−H activation of imidamides and intermolecular coupling with diazo compounds under mild conditions. The coupling of α‐diazoketoesters afforded NH indoles by cleavage of the C(N2 )−C(acyl) bond whereas α‐diazomalonates gave 3 H ‐indoles by C=N bond cleavage.